The Effects of Liquidity, Volatility, and Trading Volume on Stock Returns - Khatmi Tamtami Nisa; Mariani Salle Pasulu; Muhammad Nurwahyudi; Aini Indrijawati; Syamsuddin Syamsuddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effects of liquidity, volatility, and trading volume on stock returns for companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Research Method: This study employs a quantitative approach with an explanatory causal design. Secondary data in the form of panel data were obtained from the Indonesia Stock Exchange and Yahoo Finance. The sample was selected using purposive sampling and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, the t-test, the F-test, and the coefficient of determination. Results and Discussion: The results of the study indicate that liquidity has a significant positive effect on stock returns, volatility has a significant negative effect, and trading volume has a significant negative effect. Taken together, these three variables have a significant effect on stock returns, explaining 82.1% of the variance. Implications: These findings can serve as a basis for investors and companies when making investment decisions. Originality: This study provides empirical evidence on the simultaneous effects of liquidity, volatility, and trading volume on stock returns during the post-pandemic period in Indonesia.